One battle after another [videorecording (DVD)] - Anderson, Paul Thomas; DiCaprio, Leonardo; Penn, Sean, 1960-; Toro, Benicio del, 1967-; Hall, Regina; Taylor, Teyana, 1990-; Infiniti, Chase; Bauman, Michael (Cinematographer); Greenwood, Jonny; Atwood, Colleen; Pynchon, Thomas (Warner Bros. Entertainment Inc., 2026)
"Washed-up revolutionary Bob exists in a state of stoned paranoia, surviving off-grid with his daughter, Willa. When his evil nemesis Colonel Steven J. Lockjaw resurfaces after 16 years, they must face Bob's past and run for the future."--